Analysis of the health status and its influencing factors of the low-income populations in Wuxi, China - Li, Shiming; Jiang, Ying; Wu, Yue; Ji, Yingying; Tian, Lin; Yang, Queping; Zhu, Haohao (Frontiers in Public Health, 2024)
Objective: To understand the physical health condition and its influencing factors among the low-income population.Method: Low-income residents who visited or consulted at our Hospital during 2022 were selected for this study. Through telephone or face-to-face interviews, a self-made basic information questionnaire was used for data collection. The physical health level of the low-income population was analyzed, and a logistic regression model was applied to study its influencing factors.: A total of 2307 people were included in this study, of which 2069 had various types of diseases, indicating a disease rate of 89.68%. Multivariate logistic regression analysis showed that age ≥60 years old (OR=1.567, 95% CI:1.122 2.188), poor mental health status (OR=2.450, 95%CI:1.203 3.678), smoking (OR=1.752,95%CI:1.269 2.206), pulse pressure difference ≥60 (OR=1.485,95%CI:1.164 1.787), and poor hearing (OR=1.268,95% CI:1.026 1.324) were risk factors for disease, whereas being female (OR=0.729, 95%CI:0.540 0.984)was a protective factor for physical health.As a developing country with a large population, we should particularly focus on the physical health issues of the low-income population, take targeted measures for disease situations, and improve the quality of life of the low-income population.